Pengaruh Pertumbuhan Ekonomi dan Kemiskinan terhadap Ketimpangan di Pulau Sumatra: Analisis Data Panel Provinsi 2011–2024 - Rico Ferdian Pratama; Faqih Aji Prabowo; Tri Difastio Ramadhan; Neli Aida; Muhammad Mufti Hudani; Qurrota Ayu Nindien (CV. ITTC INDONESIA, 2025)
Inequality is caused by various factors, with one of the main contributors being the high level of poverty and the unequal distribution of economic growth across regions. There is a continuous and mutually influential relationship between poverty, economic growth, and income inequality. This study aims to analyze the impact of economic growth and poverty levels on income inequality in five provinces on the island of Sumatra: Lampung, South Sumatra, North Sumatra, West Sumatra, and Riau. The data used are secondary data obtained from the Central Bureau of Statistics (BPS) for the period 2011 to 2024. The analysis was conducted using panel data regression with a Fixed Effect Model (FEM) approach, and the data processing was carried out using EViews 12 software. The results of the study show that economic growth has a negative and significant effect on income inequality, while poverty has a positive and significant effect. Simultaneously, both variables have a significant impact on income inequality in the five provinces studied.